A Comparative Study on Beta Hedging of High PE and Low PE Stocks Using Index Futures with Reference to NSE - Mary Auxilia, P. A.; Vishwanath, G. Y.; Panneerselvam, S. (Indian Journal of Finance, 2013)
This paper analyses the hedging effectiveness of both high and low PE stocks, which are the constituents in Nifty. This study explores the difference in hedging effectiveness between high PE and low PE stocks. A hedge is highly effective if the cash flow of the hedged item and the hedging derivative offset each other to a significant extent. The portfolio was analyzed by using fortnightly data. The beta values of the stocks were determined by using the preceding six-month data, and the hedge ratio was also determined. The performance of the portfolio - both hedged and unhedged - was studied for the period from September 2010 to March 2012. Statistical parametric tests conclude that high PE stocks hedging is highly effective, and in contrast, low PE stocks hedging is not effective.